PENGARUH TERPAAN MEDIA SOSIAL INSTAGRAM AKUN @VAKSINUNTUKKITA TERHADAP TINGKAT PENGETAHUAN MASYARAKAT MENGENAI VAKSIN COVID-19 (Survei Pada Followers Instagram Vaksin Untuk Kita) - Leila Fauzia, (2022)
Behind the phenomenon of COVID-19 vaccination activities in Indonesia to achieve herd immunity, there are problems that can hinder the success of this activity, one of which is the Indonesian people's rejection of the COVID-19 vaccine. Misinformation, the lack of information about the COVID-19 vaccine circulating has caused a situation of community resistance to COVID-19 vaccination. This encourages Vaksin Untuk Kita as a movement to be present to spread information and the latest news of COVID-19 vaccination. This research using quantitative research methods, surveys, with the type of explanatory research and the Theory of Individual Differences, aims to find out how much influence the exposure of @vaksinuntukkita Instagram social media account has on the level of public knowledge about the COVID-19 vaccine. A total of 99 respondents that are followers of the Instagram account @vaksinuntukkita became the object of research. Based on the results of the correlation test, there is a strong and unidirectional relationship between the variables of social media exposure and the level of knowledge of 0.697. From the results of the coefficient of determination test, it was found that the X variable, namely exposure to social media, had an influence of 42.8% on the Y variable, namely the level of public knowledge and the remaining 57.2% was influenced by other factors outside the X and Y variables which were not examined. Through the results of hypothesis testing, it was found that the results obtained were t count 8,519 > t table 1,661 with Ha accepted. The results of this study found that there was an influence between exposure of @vaksinuntukkita Instagram social media account on the level of knowledge of followers about the COVID-19 vaccine.